Indoor climate chamber design and performance. - Garcia, Ruben A.; Santos, A.M.B.; Gunnarsen, L.
Indoor climate studies have resulted in building codes which give a positive input to the lives of people. However, knowledge about particular problems in hot and humid tropical climates is still limited. Developing countries in hot and humid regions face particular restraints in the adoption of many technical solutions to indoor climate problems. The installation and running costs of many solutions known from developed countries may be prohibitive. The Indoor Climate Laboratory is UP Mechanical Engineering's response to this need for a better quality indoor environment in tropical climates especially when resources are limited. Three climate chambers have been built and their performances are reported in this paper.